Lowering the boom : critical studies in film sound - Beck, Jay, 1966-; Grajeda, Tony, 1960- (Urbana : University of Illinois Press, 2008)
- Introduction : The future of film sound studies / Jay Beck and Tony Grajeda ##- The phenomenology of film sound : Robert Bresson's A man escaped / John Belton ##- The proxemics of the mediated voice / Arnt Maasø ##- Almost silent : the interplay of sound and silence in contemporary cinema and television / Paul Théberge ##- The sounds of "silence" : dolby stereo, sound design, and The silence of the lambs / Jay Beck ##- Sonic imagination, or, film sound as a discursive construct in Czech culture of the transitional period / Petr Szczepanik ##- Sounds of the city : Alfred Newman's "street scene" and urban modernity / Matthew Malsky ##- Film and the Wagnerian aspiration : thoughts on sound design and the history of the senses / James Lastra ##- Asynchronous documentary : Buñuel's Land without bread / Barry Mauer ##- "We'll make a Paderewski of you yet!" Acoustic reflections in The 5,000 fingers of Dr. T / Nancy Newman ##- Paul Sharit's cinematics of sound / Melissa Ragona ##- "Every beautiful sound also creates an equally beautiful picture" : color music and Walt Disney's Fantasia / Clark Farmer ##- "A question of the ear" : listening to Touch of evil / Tony Grajeda ##- "Sound sacrifices" : the post modern melodramas of World War II / Debra White-Stanley ##- Real fantasies : Connie Stevens, Silencio, and other sonic phenomena in Mulholland Drive / Robert Miklitsch ##- Selling spectacular sound : dolby and the unheard history of technical trademarks / Paul Grainge ##- (S)lip-sync : punk rock narrative film and postmodern musical performance / David Laderman ##- Criitcal hearing and the lessons of Abbas Kiarostami's Close-up / David T. Johnson ##- Rethinking point of audition in The cell / Anahid Kassabian.
Includes bibliographical references (p. [307]-326) and index.
boek
Keywords: Sound motion pictures